An Analysis of Figurative Language in the Poem Mirror by Sylvia Plath - Rahma, Awaliyah Silvia; Otong Setiawan Djauharie; Andang Saehu (Sintaksis : Publikasi Para ahli Bahasa dan Sastra Inggris, 2025)
This research explores how figurative language shapes the depth of emotion and psychology in the poem Mirror by Sylvia Plath. Through a qualitative method with a literature study approach, this research aims to identify the types of figures of speech used and explain how these elements convey the lyricist's inner conflicts related to identity, aging, and self-perception. The analysis shows that Plath consciously uses personification, metaphor, simile, and symbolism to build a reflective and emotionally charged atmosphere. The mirror in this poem is not just an inanimate object, but is present as a conscious observer who speaks, judges, and becomes a silent witness to the aging process and identity crisis of the female character. Through metaphorical and symbolic imagery, the mirror transforms into an inner lake-space that reflects the search for self. The poem closes with an evocative simile, describing the deep fear of realizing one's fading youth. This study shows that Plath's use of similes is not only to embellish the poem, but as an important channel to express fears and emotional vulnerabilities that are often difficult to verbalize. The findings are expected to enrich literary discussions on how poetic language can reveal the complexity of human experience with clarity and intensity.